Use of individualized starting dose and niraparib hematologic adverse event management costs in ovarian cancer - Whitney S Graybill; Ignace Vergote; Bhavana Pothuri; Maarit Anttila; David M O’Malley; Domenica Lorusso; Ashley F Haggerty; Michel Fabbro; John K Chan; Florian Heitz; Lyndsay J Willmott; Ilan Bruchim; et al. (Journal of Comparative Effectiveness Research)
Aim: To understand the impact of the niraparib individualized starting dose (ISD), compared with fixed starting dose (FSD), on the cost of hematologic adverse event (AE) management from a US payer perspective. Methods: The frequencies of grade ≥3 hematologic AEs that occurred in >1% of patients treated with niraparib were obtained from the primary analysis results of the phase III PRIMA/ENGOTOV26/ GOG-3012 trial. US unit costs for each grade ≥3 AE in the base case were obtained from the 2017 Agency for Healthcare Research and Quality Healthcare Cost and Utilization Project database; unit costs were adjusted to 2020 US dollars. AE management costs per patient were calculated by multiplying AE unit cost by the frequency of each AE by niraparib starting dose. Because AEs were assumed to occur independently of one another, costs were added to derive the total cost. Results: For niraparib, the estimated AEmanagement cost per patient was lower for the ISD than the FSD for all hematologic AEs (FSD vs ISD: thrombocytopenia, $4701.87 vs $1921.89; anemia, $2784.00 vs $1760.59; platelet count decreased, $2103.47 vs $922.51; neutropenia, $2112.50 vs $1369.56; neutrophil count decreased, $1285.87 vs $770.38). The total mean calculated AE management cost per patient was $12,987.71 with the FSD and $6744.93 with the ISD. Conclusion: For niraparib, the cost of managing hematologic AEs in the US was reduced by almost halfwith the ISD comparedwith the FSD. The cost reduction and improvements in safety associated with the niraparib ISD support its use in clinical practice.